2021
DOI: 10.3390/cells10061414
|View full text |Cite
|
Sign up to set email alerts
|

Contrasts in Glioblastoma—Venous Thromboembolism versus Bleeding Risk

Abstract: Glioblastoma is among the tumor entities with an extreme thrombogenic potential and patients are at very high risk of developing a venous thromboembolism (VTE) over the course of the disease, with an incidence of up to 30% per year. Major efforts are currently being made to understand and gain novel insights into the underlying pathomechanisms of the development of VTE in patients with glioblastoma and to find appropriate biomarkers. Yet, patients with glioblastoma not only face a high thromboembolic risk but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…Although some primary brain tumors such as glioblastomas are extremely thrombogenic and also pathophysiologically prone to bleeding, their increased risk of hemorrhage did not affect survival. In fact, overall survival was higher for patients receiving anticoagulation for VTE [13]. Furthermore, Burth et al showed that the use of anticoagulants did not alter the risk of intracranial hemorrhage among patients with brain tumors (both primary and metastatic) [14].…”
Section: Discussionmentioning
confidence: 99%
“…Although some primary brain tumors such as glioblastomas are extremely thrombogenic and also pathophysiologically prone to bleeding, their increased risk of hemorrhage did not affect survival. In fact, overall survival was higher for patients receiving anticoagulation for VTE [13]. Furthermore, Burth et al showed that the use of anticoagulants did not alter the risk of intracranial hemorrhage among patients with brain tumors (both primary and metastatic) [14].…”
Section: Discussionmentioning
confidence: 99%
“…High-grade glioma (HGG), particularly grade IV that includes glioblastoma (GBM), is the most aggressive form of primary brain tumors, with GBM being associated with one of the highest risks of VTE (20%-30%) systemically (41,47). Moreover, GBMs manifest a consistent (and diagnostic) presence (~90%) of intratumoral microthrombosis (48)(49)(50)(51)(52). This is contrasted by a VTE risk of 8.2% for grade II and 9.2% for grade III gliomas (41) with correspondingly lower frequency of microthrombosis (52).…”
Section: Oncogenes and Vte Effectorsmentioning
confidence: 99%